Inhibition by Tranilast of the Synergistic Induction of Degranulation and IL-13 Expression by IL-33 and FcɛRI Cross-linking in Mast Cells. (2nd November 2017) - Tsuji, Kazuhiro; Fukuda, Ken; Fukushima, Atsuki
ABSTRACT: Purpose : To assess the effects of tranilast on degranulation and IL-13 production in mast cells activated by IL-33 and cross-linking of FcɛRI. Methods : Bone marrow-derived mast cells (BMMCs) were sensitized with anti-DNP IgE. Sensitized cells were pretreated with tranilast and further stimulated with DNP-BSA, IL-33, or a combination of DNP-BSA and IL-33. Degranulation and the level of IL-13 release and mRNA expression in BMMCs were measured. Results : Simultaneous stimulation with DNP-BSA and IL-33 resulted in marked increase in β-hexosaminidase release. Tranilast significantly inhibited degranulation of BMMCs in the condition of combined treatment of DNP-BSA and IL-33. Combination of DNP-BSA and IL-33 induced a pronounced increase in the IL-13 release and mRNA expression. Tranilast significantly inhibited IL-13 release and mRNA expression in BMMCs stimulated by DNP-BSA and IL-33. Conclusions : Tranilast has efficacy on the inhibition of degranulation and IL-13 production in BMMCs induced by the combination of DNP-BSA and IL-33.